Does Loudness Relate to the Strength of the Sound Produced by the Source or Received by the Ears? A Review of How Focus Affects Loudness - Berthomieu, Gauthier; Koehl, Vincent; Paquier, Mathieu (Frontiers in Psychology, 2021)
Loudness is the magnitude of the auditory sensation that a listener experiences when exposed to a sound. Several sound attributes are reported to affect loudness, such as the sound pressure level at the listener's ears and the spectral content. In addition to these physical attributes of the stimulus, some subjective attributes also appear to affect loudness. When presented with a sound, a listener interacts with an auditory object and can focus on several aspects of the latter. Loudness appears to differ depending on how listeners apprehend this object, notably whether they focus on the sound that reaches their ears or that is produced by the source. The way listeners focus on the auditory object may depend on the stimulus itself. For instance, they might be more likely to focus on the sound emitted by the source if the latter is visible. The instructions given by the experimenters can also explicitly direct the listener's focus on the sound reaching the ears or emitted by the source. The present review aims at understanding how listeners focus on the auditory object depending on the stimuli and instructions they are provided with, and to describe how loudness depends on this focus.